2018
DOI: 10.18535/jmscr/v6i1.05
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant EDTA Induced Storage effect (Artifacts) on Peripheral Blood Cells

Abstract: Aims & Objectives: The EDTA induced RBC & WBC morphological storage artifacts. Identify the EDTA induced platelets related artifacts. Exclude the EDTA induced storage artifacts. Identify and exclude the misinterpretation of peripheral blood smears examination.Material & Methods: Blood was collected in a sterile EDTA containing tube and processed following our established laboratory protocol. A complete blood counting including HB%, PCV, Red cell indices, platelet count and total white cell count and differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…EDTA induced pseudo agglutination of platelets initiated at 3 hrs and marked at 6hrs no significant platelet aggregation was observed with citrate blood. The findings correlates with Koolwal and Chavda et al 7,8 Other artefacts like smudge cells, increase in size of WBCS, crenated RBC's and abnormal staining were also observed which began as early as 1 hr with citrate but delayed upto 3-4hrs with EDTA blood. Similar findings were noted by Narasimha et al 11 All these changes can be misinterpreted as pathological findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…EDTA induced pseudo agglutination of platelets initiated at 3 hrs and marked at 6hrs no significant platelet aggregation was observed with citrate blood. The findings correlates with Koolwal and Chavda et al 7,8 Other artefacts like smudge cells, increase in size of WBCS, crenated RBC's and abnormal staining were also observed which began as early as 1 hr with citrate but delayed upto 3-4hrs with EDTA blood. Similar findings were noted by Narasimha et al 11 All these changes can be misinterpreted as pathological findings.…”
Section: Discussionsupporting
confidence: 88%
“…Following changes were observed: Nuclear Changes: Initially lobulations were observed as early as 2hrs followed by nuclear degeneration, karyolysis, nuclear vacuolations and nuclear rupture which began as early as 0hrs with citrate. Similar findings were noted by Koolwal, Vajpayee and Raphael et al 7,9,10 Cytoplasmic Changes: cytoplasmic vacuoles began to occur as early as 0hrs with sodium citrate with completely altered morphology including hairy projections, blebs and rupture at the end of 6hrs. The changes are delayed upto 2hrs with EDTA blood.…”
Section: Discussionsupporting
confidence: 81%
“…Our study identified the following bands: 741, 1123, 1350, 1578, and 1618 cm −1 ; these are associated with the following vibrational modes and compounds: vibration of the tryptophan ring, asymmetric C-O-C stretching of glucose, C-H curve of tryptophan, C=C stretching of the heme group, and C-N stretching of the heme group, respectively [70][71][72].…”
Section: Ultrastructural Analysis Of the Blood Samples Raman Spectros...mentioning
confidence: 71%
“…Raman spectra of erythrocytes mainly showed bands corresponding to the vibrational modes of hemoglobin [70] and in some cases it is possible to detect bands corresponding to components of the erythrocyte membrane. The bands associated with rat erythrocytes can be found at 42,1001,1123,1247,1341,1368,1446,1576, and 1619 cm −1 , and derived from compounds such as hemoglobin, albumin, and glucose [71].…”
Section: Ultrastructural Analysis Of the Blood Samples Raman Spectros...mentioning
confidence: 99%
“…Thirdly, the preservation time is long. The preservation time of peripheral blood in the low-temperature environment is long and the detection is less affected by environmental factors ( 39 ).…”
Section: Discussionmentioning
confidence: 99%